A Solution-Processable, Nanostructured, and Conductive Graphene/Polyaniline Hybrid Coating for Metal-Corrosion Protection and Monitoring. Issue 1 (December 2017) - Kim, Saerona; Le, Thanh-Hai; Park, Chul; Park, Geunsu; Kim, Kyung; Kim, Semin; Kwon, Oh; Lim, Gyun; Yoon, Hyeonseok
Abstract A smart and effective anticorrosive coating consisting of alternating graphene and polyaniline (PANI) layers was developed using top-down solution processing. Graphite was exfoliated using sonication assisted by polyaniline to produce a nanostructured, conductive graphene/polyaniline hybrid (GPn) in large quantities (>0.5 L of 6 wt% solution in a single laboratory-scale process). The GPn was coated on copper and exhibited excellent anticorrosion protection efficiencies of 46.6% and 68.4% under electrochemical polarization in 1 M sulfuric acid and 3.5 wt% sodium chloride solutions, chosen as chemical and seawater models, respectively. Impedance measurements were performed in the two corrosive solutions, with the variation in charge transfer resistance (R ct ) over time indicating that the GPn acted as an efficient physical and chemical barrier preventing corrosive species from reaching the copper surface. The GPn-coated copper was composed of many PANI-coated graphene planes stacked parallel to the copper surface. PANI exhibits redox-based conductivity, which was facilitated by the high conductivity of graphene. Additionally, the GPn surface was found to be hydrophobic. These properties combined effectively to protect the copper metal against corrosion. We expect that the GPn can be further applied for developing smart anticorrosive coating layers capable of monitoring the status of metals.